Clinical indications for penetrating keratoplasty in Maharaj Nakorn Chiang Mai Hospital, 1996-1999 - Chaidaroon W. (2014)
Purpose: To determine the leading indication for penetrating keratoplasty. Material and Method: The authors retrospectively performed a chart review of the hospital records of all patients who underwent penetrating keratoplasty at Maharaj Nakorn Chiang Mai Hospital between January 1996 and December 1999. Results: A total of 45 corneal transplants were performed. The leading indications for penetrating keratoplasty, in order of decreasing frequency, were bullous keratopathy (28.9%), corneal scar (22.2%), corneal dystrophy and degeneration (20.0%), corneal ulcer (17.8%), regraft (8.9%), and trauma (2.2%). Conclusion: Bullous keratopathy was the leading indication for penetrating keratoplasty at Maharaj Nakorn Chiang Mai Hospital from 1996 to 1999, followed by corneal scar. The major cause of bullous keratopathy was associated with posterior chamber intraocular lens implantation.